2006
DOI: 10.1348/096317905x55271
|View full text |Cite
|
Sign up to set email alerts
|

Testing causal models of job characteristics and employee well‐being: A replication study using cross‐lagged structural equation modelling

Abstract: This study re‐evaluated causal relationships between job characteristics (demands, autonomy, social support) and employee well‐being (job satisfaction, emotional exhaustion) in a methodological replication of De Jonge et al. 's (2001) two‐wave panel study. The principal difference was the 2‐year time lag between measurements in this study versus a 1‐year time lag in the original study. Three competing causal models were compared: regular causation (job characteristics influence well‐being); reverse causation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 16 publications
1
34
1
2
Order By: Relevance
“…In terms of sampling strategy, studies either recruited workers from a specific profession (eg, dentists) or the same work organization (eg, a bank) or utilized data from regional registries (included diverse types of workers). Workers in healthcare settings (eg, clinicians and support staff) were investigated most often (N=10) (50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Of the 18 studies originating from Europe (22, 29, 50-52, 54-67), 14 were from The Netherlands.…”
Section: Methodological Properties Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of sampling strategy, studies either recruited workers from a specific profession (eg, dentists) or the same work organization (eg, a bank) or utilized data from regional registries (included diverse types of workers). Workers in healthcare settings (eg, clinicians and support staff) were investigated most often (N=10) (50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Of the 18 studies originating from Europe (22, 29, 50-52, 54-67), 14 were from The Netherlands.…”
Section: Methodological Properties Of Studiesmentioning
confidence: 99%
“…Sixteen studies featured two measurement waves (50-56, 58-63, 65, 68, 70), four featured three waves (57,66,67,69), two featured four waves (22,64), and one study featured six measurement waves (29). Of note, eight studies explicitly indicated that job changers (over the course of the study) were excluded from analysis (52,56,57,59,64,65,67,70). The 23 qualifying studies also featured varied com- binations of stressor/strain variables.…”
Section: Methodological Properties Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence for the relationship between challenge type stressors and job satisfaction is inconclusive. While some studies report a positive effect (Beehr, Glaser, Canali, & Wallwey, 2001;Boswell, Olson-Buchanan, & LePine, 2004;LePine et al, 2005;Podsakoff et al, 2007;Webster, Beehr, & Christiansen, 2010), others find the relationship to be negative or insignificant (e.g., de Lange, Taris, Kompier, Houtman, & Bongers, 2004;Doest & Jonge, 2006). Thus, we believe it is important to provide further evidence of the additive and interactive effects of challenge stress upon job satisfaction.…”
Section: Theoretical Backgroundmentioning
confidence: 86%
“…The study also supported the use of people related TQM practices to be incorporated as a model of the HR system in organisations. Doest and Jonge (2006) re-estimated the causal relationships between job characteristics (demands, autonomy and social support) and employee well-being (job satisfaction and emotional exhaustion). The three challenging causal models (regular, reverse and reciprocal) were compared and at the end, regular causation offered the best account as in the previous case.…”
Section: Job Satisfactionmentioning
confidence: 99%